THE RELATIONSHIP OF BASIC CLINICAL STATUS WITH THE QUALITY OF LIFE OF HIV AND AIDS PATIENTS - Lilis Masyfufah; Erwin Astha Triyono (Universitas Airlangga, 2020)
Background: The success of individual antiretroviral drug (ARV) treatment in patients with human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) was determined by conducting a routine evaluation of the patients’ Cluster of Differentiation 4 (CD4) count. The indicators used to measure the success of the HIV and AIDS treatment were mortality, mobility, and quality of life (QoL). Purpose: The purpose of this research was to analyze the relationship between clinical status (smoking status, duration of ARV therapy, the CD4 count, and body mass index [BMI]) and the QoL of patients with HIV and AIDS who were stable during treatment. Methods: This type of research was quantitative analytical research with a cross-sectional design. This research was conducted at Dr. Soetomo Hospital, Surabaya, from September to November 2017. The study population was patients with HIV and AIDS in Dr. Soetomo Hospital, Surabaya. The research sample was taken by purposive sampling with the inclusion criteria being patients with HIV and AIDS who had been treated for ≥6 months with adherence ≥95% and who came directly to the hospital. Results: The majority of respondents were female (53.36%), junior/senior high school graduates (66.67%), married (62.22%), non-smoking (75.56%), had undergone ARV therapy for ±10 years (77.78%), and had a QoL in the adequate category (62.22%). The basic clinical status with a significant relationship with the respondents’ QoL were the CD4 count (p = 0.00) and BMI (p = 0.00). Conclusion: There was a relationship of the CD4 count and BMI with the QoL of the patients with HIV and AIDS.